Evaluation of the Effect of Aneurysmal Clipping on Electrocardiography and Echocardiographic Changes in Patients With Subarachnoid Hemorrhage: A Prospective Observational Study. Issue 3 (July 2017) - Jangra, Kiran; Grover, Vinod K.; Bhagat, Hemant; Bhardwaj, Avanish; Tewari, Manoj K.; Kumar, Bhupesh; Panda, Nidhi B.; Sahu, Seelora
Abstract : Background: Electrocardiographic (ECG) and echocardiographic changes that are subsequent to aneurysmal subarachnoid hemorrhage (a-SAH) are commonly observed with a prevalence varying from 27% to 100% and 13% to 18%, respectively. There are sparse data in the literature about the pattern of ECG and echocardiographic changes in patients with SAH after clipping of the aneurysm. Hence, we observed the effect of aneurysmal clipping on ECG and echocardiographic changes during the first week after surgery, and the impact of these changes on outcome at the end of 1 year. Materials and Methods: This prospective, observational study was conducted in 100 consecutive patients with a-SAH undergoing clipping of ruptured aneurysm. ECG and echocardiographic changes were recorded preoperatively and every day after surgery until 7 days. Outcome was evaluated using the Glasgow outcome scale at the end of 1 year. Results: Of 100 patients, 75 had ECG changes and 17 had echocardiographic changes preoperatively. The ECG changes observed were QTc prolongation, conduction defects, ST-wave and T-wave abnormalities, tachyarrhythmias, and bradyarrhythmias. The echocardiography changes included global hypokinesia and regional wall motion abnormalities. Both echocardiographic and ECG changes showed significant recovery on the first postoperative day. Patients presenting with both echocardiographic and ECG changes were found to require higher ionotropic support to maintain the desired blood pressure, and were associated with poor outcome (Glasgow outcome scale, 1 to 2) at 1 year after surgery. There was no association of ECG and echocardiographic changes with mortality (both in-hospital or at 1 year). Conclusions: The ECG changes, such as QTc prolongation, bradycardia, conduction abnormality, and echocardiographic changes, recover on postoperative day-1, in most of the cases after clipping. Patients with combined ECG and echocardiographic changes tend to have poor neurological outcome at the end of 1 year.